BERAPA JUMLAH PENGUNJUNG YANG SEHARUSNYA DITERIMA OLEH PENGUSAHA PARIWISATA PADA SAAT PANDEMI COVID-19? - Suasapha, Anom Hery; Tirtawati, Ni Made; Dianasari, Dewa Ayu Made Lily; Iswarini, Ni Ketut; Sudiarta, I Nyoman (Paryaṭaka Jurnal Pariwisata Budaya dan Keagamaan, 2025)
Limiting the number of visitors is one of the best efforts that tourism entrepreneurs can make to continue operating safely during the COVID-19 pandemic. Unfortunately, a method for determining the maximum number of visitors accepted during an outbreak is unavailable. This article explains the method to determine the maximum number of visitors using a seafood café in Kedonganan Beach Bali as a case study. The proposed determination method uses a tourism carrying capacity formula that is modified by incorporating physical distancing and correction factors relevant to the COVID-19 pandemic situation, such as temporary closure of destination, attraction, and tourism business, into the equation. This article demonstrates how modifications made to the original carrying capacity formula can produce a formula for determining the maximum number of visitors that can be received during the pandemic while placing the visitors’ and workers' safety as a top priority. This article shows how the modified formula can calculate the maximum number of visitors the tourism operator can accept during the COVID-19 Pandemic. This article contributes an idea in developing a method for determining the maximum number of visitors in the future if the tourism industry faces a similar situation where tourist movement and interaction, as the essence of tourism, can threaten their safety.